Biosecurity practices in the dairy farms of southern Brazil - Ferreira, Janaína Santos; Baccili, Camila Costa; Nemoto, Beatriz S.; Vieira, Fabiano Koerich; Sviercoski, Leonardo Moreira; Ienk, Tanaane; Pagno, Jefferson Tramontini; Gomes, Viviani (Frontiers in Veterinary Science, 2024)
Biosecurity refers to a set of practices that prevents and/or controls the introduction, spread, and elimination of harmful biological agents in a production system. In this study, we aimed to survey the biosecurity practices and determine their correlation with the size of production systems. A biosecurity assessment form was provided to 69 farms in the Campos Gerais region of Paraná, Brazil. The questionnaire was divided into two sections: general and bovine viral diarrhea virus- and bovine herpesvirus type-1-specific sections. The general section covered topics on traffic control, quarantine and animal isolation, hygiene practices, carcass disposal, and disease monitoring/control. The specific section consisted of questions on the reproductive and respiratory factors, use of antimicrobials, and vaccination schedule. The 69 farms were also classified into small (≤ 61), medium (62–201), and large (≥ 202) size farms based on the number of lactating cows. Moreover, multiple correspondence analysis (MCA) was performed between the biosecurity measures and farm size. The main risk factors and variability were related to the traffic control of people, animals, and vehicles/equipment, animal quarantine/isolation, and hygiene practices. MCA revealed that the small farms exhibited a lack of biosecurity measures, including those related to traffic control, animal quarantine, and hygiene. In medium-size farms, contact between bovine animals of different ages and difficulty in animal isolation in the quarantine system were among the main risk factors. In contrast, isolation of sick animals was easy, but the need to frequently purchase cattle was an important risk factor in large farms. These results highlight the relationship between biosecurity measures and farm size, providing valuable insights for the development of better biosecurity plans for production systems.